Exenatide once-weekly injection for the treatment of type 2 diabetes in Chinese patients: current perspectives - Deng W; Qiu S; Yang G; Chen B (Dove Medical Press, 2015)
Wuquan Deng,1,* Sheng Qiu,1,* Gangyi Yang,2 Bing Chen1 1Department of Endocrinology, Southwest Hospital, Third Military Medical University, 2Department of Endocrinology, Second Affiliated Hospital, Chongqing Medical University, Chongqing, People’s Republic of China *These authors contributed equally to this work Abstract: Glucagon-like peptide-1 (GLP-1) analogs, such as exenatide, have played an important role as antidiabetic medications in the treatment of type 2 diabetes (T2DM). Like most other hypoglycemic agents, exenatide has a number of actions, including lowering blood glucose, promoting weight loss, improving insulin resistance, and protecting islet β-cells. Although GLP-1 analogs, combined with other antidiabetic medications, have excellent performance in T2DM, some side effects and imperfections limit its use in clinical practice. Since 2012, a new generation GLP-1 agent, exenatide once weekly (QW), has been available for patients with T2DM in the USA, but not as yet in the People’s Republic of China. Previous data indicate that exenatide QW achieves better fasting glucose reductions than sitagliptin or exenatide twice daily, whilst appearing non-inferior to pioglitazone and achieving less reductions than insulin glargine. Exenatide QW was better at improving average postprandial glucose than sitagliptin or titrated insulin glargine, but was inferior to exenatide twice daily. Additionally exenatide QW has a better effect in terms of weight loss than other glycemic medications. Exenatide QW can also reduce blood lipids and lower blood pressure. Accordingly, exenatide QW is cost-effective, achieves good clinical outcomes, and has acceptable side effects, indicating that it has promising prospects for future use in the People’s Republic of China. Keywords: diabetes, glycemic control, exenatide once weekly